2015
DOI: 10.1039/c4ra12747a
|View full text |Cite
|
Sign up to set email alerts
|

Facial synthesis of hexagonal metal oxide nanoparticles for low temperature ammonia gas sensing applications

Abstract: A surfactant assisted facial hydrothermal process has been employed for the synthesis of rutile and wurztile phase SnO 2 and ZnO nanoparticles, respectively, confirmed by X-ray diffraction studies. High resolution transmission electron microscopy studies revealed the formation of ~15 and 20 nm of SnO 2 and ZnO nanoparticles, respectively, whereas, the structural analysis was done via Fourier transform infrared (FTIR) and Raman spectroscopy studies that suggested the minor doping of surfactant and surface adsor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(31 citation statements)
references
References 39 publications
2
29
0
Order By: Relevance
“…Raman spectrum (Figure b) of the anodic film fabricated without F − (Sample 1:0) exhibited two peaks at 306 and 467 cm −1 , corresponding to the Eu(TO) and E g vibrations of SnO 2 , and three typical peaks at 215, 146, and 119 cm −1 , corresponding to the A 1g , E g , and B 1g vibrational modes of SnO . For Sample 2:1, a lower peak at 306 cm −1 was observed, indicating the reduced content of SnO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Raman spectrum (Figure b) of the anodic film fabricated without F − (Sample 1:0) exhibited two peaks at 306 and 467 cm −1 , corresponding to the Eu(TO) and E g vibrations of SnO 2 , and three typical peaks at 215, 146, and 119 cm −1 , corresponding to the A 1g , E g , and B 1g vibrational modes of SnO . For Sample 2:1, a lower peak at 306 cm −1 was observed, indicating the reduced content of SnO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, these structural parameters have been evaluated for all three sets of films. The well known Debye-Scherrer's formula [18][19][20][21] given below is used to determine the crystallite size,…”
Section: Structural and Morphological Studiesmentioning
confidence: 99%
“…It is observed that the crystallite size of the deposited film at 400 o C increases slightly with increase in annealing temperature to 500 and 600 o C. This is because of that the annealing temperature provides the necessary energy for crystallization and adjustment of atoms/molecules of the film for the formation long order crystal structure. The calculated average crystallite sizes for the deposited films are further used to examine the average defect density in the films using the relation [18,19]…”
Section: Structural and Morphological Studiesmentioning
confidence: 99%
“…It has been shown that the sensing selectivity and sensitivity of ZnO for toxic gases and VOCs are strongly dependent on ZnO's structure and morphology . Hence, recent research efforts have focused on the development of ZnO with controlled structure and morphology, for example, nanoparticles, nanorods, nanoflowers, nanopencils, and 2D nanogrids . Some recent research works have shown that these types of nanostructured ZnO materials exhibit improved performance for the detection of gaseous substances and VOCs, and also catalyze reactions such as hydrazine oxidation and hydrogen peroxide reduction, reactions that can be taken advantage of for the detection of various chemical agents.…”
Section: Figurementioning
confidence: 99%